A new lepto-hadronic model applied to the first simultaneous multiwavelength data set for Cygnus X–1. Issue 2 (29th October 2020) - Kantzas, D; Markoff, S; Beuchert, T; Lucchini, M; Chhotray, A; Ceccobello, C; Tetarenko, A J; Miller-Jones, J C A; Bremer, M; Garcia, J A; Grinberg, V; Uttley, P; et al.
ABSTRACT: Cygnus X–1 is the first Galactic source confirmed to host an accreting black hole. It has been detected across the entire electromagnetic spectrum from radio to GeV gamma-rays. The source's radio through mid-infrared radiation is thought to originate from the relativistic jets. The observed high degree of linear polarization in the MeV X-rays suggests that the relativistic jets dominate in this regime as well, whereas a hot accretion flow dominates the soft X-ray band. The origin of the GeV non-thermal emission is still debated, with both leptonic and hadronic scenarios deemed to be viable. In this work, we present results from a new semi-analytical, multizone jet model applied to the broad-band spectral energy distribution of Cygnus X–1 for both leptonic and hadronic scenarios. We try to break this degeneracy by fitting the first-ever high-quality, simultaneous multiwavelength data set obtained from the CHOCBOX campaign (Cygnus X–1 Hard state Observations of a Complete Binary Orbit in X-rays). Our model parametrizes dynamical properties, such as the jet velocity profile, the magnetic field, and the energy density. Moreover, the model combines these dynamical properties with a self-consistent radiative transfer calculation including secondary cascades, both of leptonic and hadronic origin. We conclude that sensitive TeV gamma-ray telescopes like Cherenkov Telescope Array (CTA) will definitively answer the question of whether hadronic processes occur inside the relativistic jets of Cygnus X–1.